2008
DOI: 10.2214/ajr.07.3534
|View full text |Cite
|
Sign up to set email alerts
|

Causes of TIPS Dysfunction

Abstract: Biologic and technical factors may predispose to shunt failure. The combination of improved technique and expandable PTFE has significantly improved TIPS patency. The need for follow-up venography and secondary interventions has been reduced significantly as a result of improved shunt patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 36 publications
2
59
2
1
Order By: Relevance
“…In this study, we carefully assessed TIPS stent dysfunction through hemodynamic measurements and strict long-term clinical follow-up. Our results are in accordance with other studies in terms of stent patency rate and location of stenosis (8)(9)(10)(11)(12)(13)(14)27). Notably, we first revealed that portal trunk access (P = 0.006; OR 2.56; 95% CI, 1.3 -5.04) was the only independent risk factor of TIPS dysfunction in multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, we carefully assessed TIPS stent dysfunction through hemodynamic measurements and strict long-term clinical follow-up. Our results are in accordance with other studies in terms of stent patency rate and location of stenosis (8)(9)(10)(11)(12)(13)(14)27). Notably, we first revealed that portal trunk access (P = 0.006; OR 2.56; 95% CI, 1.3 -5.04) was the only independent risk factor of TIPS dysfunction in multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…TIPS dysfunction is related to three common causes: acute thrombosis, pseudointimal hyperplasia in the intraparenchymal segment of the stent, and intimal hyperplasia of the hepatic vein outflow tract (16)(17)(18). The incidence of stent dysfunction in patients with TIPS created with bare metal stents is approximately 25% after 6 months or 50% after 1 year (8)(9)(10)(11)(12)(13)(14). To maintain TIPS patency, it is prudent to regularly monitor the shunt with Doppler ultrasound and eventually direct portography with frequent secondary intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bare metal stent stenosis is described as pseudointimal hyperplasia as a result of fistulas between the shunt and bile ducts. Second, stenosis can occur at the hepatic vein due to intimal hyperplasia caused by chronic injury from increased highvelocity blood flow (16). Given the fact that TIPS malfunction is relatively frequent with bare metal stents and because of the success of shunt revision, it is crucial to detect stenosis before recurrence of clinical symptoms.…”
Section: Sonographic Assessment After Tips Placementmentioning
confidence: 99%